Addressing Obstacles to Poor English Reading Comprehension in Fifth-Graders: Employing Metacognitive Strategies for Improvement - Nida Ayaz ,; Dr. Abdul Ghaffar,; Dr. Muhammad Idris, (Dialogue Social Science Review (DSSR), 2025)
This study uncovers the underlying factors contributing to subpar English reading comprehension among primary students. Its objective is to propose recommendations for enhancing students' proficiency in English reading comprehension. Employing action research, a group of 30 fifth-grade students, aged ten to eleven, was selected for examination. Data collection involved interviews, documentation, and observation, with content analysis and reflection employed for data analysis. Various factors, such as insufficient vocabulary knowledge, a tendency to cram, and a lack of interest in developing creative reading skills beyond test performance, were identified as reasons for low English reading comprehension. To improve students' reading comprehension skills, fostering motivation for learning to read is crucial. As a result, it is imperative for educational authorities to conduct periodic training and seminars for teachers, increasing their awareness of factors contributing to poor reading comprehension and instructing them on how to address these issues through the application of metacognitive strategies in the classroom. Additionally, it is recommended that future researches may focus on strategies, beyond metacognitive ones, that contribute to the development of strong comprehension abilities.